The ethnozoology of Jering ethnic society in utilizing the animals for halal traditional medicine - Yola Nazelia Nukraheni; Budi Afriansyah; Muhammad Ihsan (Universitas Airlangga, 2019)
Bangka island province has a high diversity of culture and local wisdom from its ethnic, one of them is Jerieng ethnic. Jerieng ethnic is tribe comes from Bangka Barat, especially Simpang Teritip subdistrict. Jerieng ethnic has knowledge in utilization biodiversity such as an animal that is utilized to be traditional medicine, This study is aimed to discover the knowledge of Jerieng ethnic about which animal used, knowing the method. to utilize it as traditional medicine and sort it into halal and haram based on Islamic law. The method used in this study is purposive sampling, include preliminary, data and information collecting, identification and grouping into halal and haram. Animals that are often used there are 21 species, 10 species (48%) categorized as halal and 11 species (52%) categorized as haram.